Improvement of bearing capacity of strip footing on reinforced sand. Issue 6 (2nd November 2018) - Benmebarek, Sadok; Djeridi, Safa; Benmebarek, Naïma; Belounar, Lamine
Abstract : In this paper, numerical computations using FLAC code are carried out to develop a new practical reinforcement technique using geosynthetic reinforcement to increase the load bearing capacity of shallow foundations on a sand soil. In all previous works, the method of reinforcing soil with layers of individual reinforcements placed horizontally within the soil mass to support shallow foundations. This paper aims to present the details of numerical analysis of strip footing resting on a reinforced sand bed with horizontal layer (s) and horizontal layers with full wrap-around ends of geotextile to increase the capacity of shallow foundations. Order to show more clearly the performance of the full wraparound ends of reinforcement compared to that of reinforcement placed horizontally, the effect of different parameters contributing to their performance such as burial depth, width and tensile stiffness of geotextile on the increase of the bearing capacity were studied. The results indicate that the full wraparound ends solution for reinforced gave a significant improvement in the bearing capacity and saving in the land space to construct a reinforced sand bed system and the proposed full wrap-around ends need less quantity of geotextile than planar geotextile placed horizontally.